Blowup for a time-oscillating nonlinear heat equation - Cazenave, Th; Escobedo, M.; Zuazua, Enrique (Acta Mathematica Universitatis Comenianae, 2013)
In this paper, we study a nonlinear heat equation with a periodic time oscillating term in factor of the nonlinearity. In particular, we give examples showing how the behavior of the solution can drastically change according to both the frequency of the oscillating factor and the size of the initial value.
CRIS-Team Scopus Importer:2021-06-15
Keywords: Finite-time blowup; Semilinear heat equation; Time-oscillating nonlinearity